2014
DOI: 10.1186/1471-2318-14-97
|View full text |Cite
|
Sign up to set email alerts
|

Fighting for control in an unpredictable life – a qualitative study of older persons’ experiences of living with chronic dizziness

Abstract: BackgroundDizziness in older people is associated with disability and reduced quality of life. Few studies have investigated how daily life is affected from the older person’s perspective. Identifying barriers and resources in daily life could guide health care in how to direct efficient interventions. The aim of this study was to explore older persons’ experiences of living with chronic dizziness.MethodsIn this qualitative study seven women aged 74–84 years and six men aged 73–87 years with chronic dizziness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…The underlying causes of falls are multifaceted [ 2 ] and the informants identified known risk factors like aging [ 4 ], muscle and neurological diseases [ 3 ], and environmental factors like furniture, carpets and slippery surface [ 2 ] as risk factors for falls. To not consider themselves susceptible to falls and to mainly recognize exterior factors to cause falls [ 12 ] and to fight for a normal life style when occasionally feeling dizzy have also been found by others [ 10 ]. This is in line with the finding that some of our informants downplayed their fall risk [ 13 ] or dizziness [ 8 ] since they were eager to emphasize what they still managed in everyday life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying causes of falls are multifaceted [ 2 ] and the informants identified known risk factors like aging [ 4 ], muscle and neurological diseases [ 3 ], and environmental factors like furniture, carpets and slippery surface [ 2 ] as risk factors for falls. To not consider themselves susceptible to falls and to mainly recognize exterior factors to cause falls [ 12 ] and to fight for a normal life style when occasionally feeling dizzy have also been found by others [ 10 ]. This is in line with the finding that some of our informants downplayed their fall risk [ 13 ] or dizziness [ 8 ] since they were eager to emphasize what they still managed in everyday life.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of dizziness has been reported by 17.5% for the age group 60–80 years and 31.0% for those above 80, with a higher prevalence in women [ 9 ]. Studies of elderly’s experiences of living with dizziness found that they fought to live a normal life [ 10 ], to understand the causes [ 8 ] and also to get accurate information in order to handle or control the dizziness [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dizziness can refer to several sensations including a giddy or rotational sensation, a loss of balance, a faint feeling, light-headedness, instability or unsteadiness, a tendency to fall, or a feeling of everything turning black [ 7 ]. It is well-known that dizziness strongly affects daily living of older people [ 8 11 ]. Dizziness has moderate or severe impact on daily living of more than 60 % of older people with dizziness in primary care [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“… 2 Qualitative studies have highlighted the impact of dizziness on everyday life, often leading to poor function and disability. 3 4 Dizziness is more common in older people, but it is estimated that 1 in 10 working-age adults suffer some degree of disability due to dizziness. 5 Significant disability, medication use and medical consultations due to dizziness have been found in more than 20% of people over the age of 60, 6 with 24% of dizziness being attributed to vestibular disorder.…”
Section: Introductionmentioning
confidence: 99%
“…11 15 Furthermore, many patients with chronic dizziness have unmet healthcare needs. 3 Vestibular rehabilitation (VR) is now the recommended treatment for dizziness. 15 16 The central component of VR is a programme of graded exercises consisting of eye, head and body movements designed to stimulate the vestibular system and promote neurological adaptation.…”
Section: Introductionmentioning
confidence: 99%